MERCEOLOGIA: A NEW FIELD FOR CHEMISTS AND CHEMICAL ENGINEERS - García P., J. M. (2010)
The merceologia is the discipline that studies the classification of goods by either animal, vegetable or mineral or function, according to the Harmonized Commodity Description and Coding System - SA, based on the following questions: what is it?; what is done?; what is? bearings allowing the correct classification, and for this reason that according to the characteristics of the training chemists and chemical engineering to merceologia proposed as an elective.